2009
DOI: 10.1074/jbc.m806486200
|View full text |Cite
|
Sign up to set email alerts
|

Type II cGMP-dependent Protein Kinase Mediates Osteoblast Mechanotransduction

Abstract: Continuous bone remodeling in response to mechanical loading is critical for skeletal integrity, and interstitial fluid flow is an important stimulus for osteoblast/osteocyte growth and differentiation. However, the biochemical signals mediating osteoblast anabolic responses to mechanical stimulation are incompletely understood. In primary human osteoblasts and murine MC3T3-E1 cells, we found that fluid shear stress induced rapid expression of c-fos, fra-1, fra-2, and fosB/⌬fosB mRNAs; these genes encode trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 92 publications
(115 citation statements)
references
References 95 publications
6
108
0
1
Order By: Relevance
“…FSS increases NO production rapidly through calcium activation of NO synthase(s), although enhanced NO synthesis may be sustained through calcium-independent mechanisms (6,(11)(12)(13). NO synthase inhibitors block FSS-induced bone formation and c-fos mRNA expression in vivo, and experiments in NO synthase-deficient mice suggest a crucial role of NO in osteoblast mechanotransduction (14 -17).…”
Section: Mechanical Loading Of Bone Induces Interstitial Fluid Flow mentioning
confidence: 99%
“…FSS increases NO production rapidly through calcium activation of NO synthase(s), although enhanced NO synthesis may be sustained through calcium-independent mechanisms (6,(11)(12)(13). NO synthase inhibitors block FSS-induced bone formation and c-fos mRNA expression in vivo, and experiments in NO synthase-deficient mice suggest a crucial role of NO in osteoblast mechanotransduction (14 -17).…”
Section: Mechanical Loading Of Bone Induces Interstitial Fluid Flow mentioning
confidence: 99%
“…Although the NO/cGMP pathway may work as either stimulatory or inhibitory on ERK depending on the cell types, 29,30 a puzzling question remains unanswered as to why the NO/cGMP pathway, acting as the downstream mediator of Ang II signaling, exerts the contrasting effects on PT transport in humans and other species. However, several previous studies have suggested that such species differences may, indeed, exist in the roles of the NO/cGMP pathway in renal sodium handling.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent data show that this kinase has some new functions: Nie et al (18) found that PKGII regulated epithelial sodium channels; Rangaswami et al (19,20) reported that PKGII had an important role in mechano-transduction of osteoblast. A more important finding in research of PKGII is that this kinase has a role in regulating proliferation and apoptosis of cells and is potentially associated with tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%